2020
DOI: 10.48550/arxiv.2006.04601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FRB 200428: an Impact between an Asteroid and a Magnetar

Jin-Jun Geng,
Bing Li,
Long-Biao Li
et al.

Abstract: A fast radio burst was recently detected to be associated with a hard X-ray burst from the Galactic magnetar SGR 1935+2154. Scenarios involving magnetars for FRBs are hence highly favored. In this work, we suggest that the impact between an asteroid and a magnetar could explain such a detection. According to our calculations, an asteroid of mass 10 20 g will be disrupted at 7 × 10 9 cm when approaching the magnetar, the accreted material will flow along the magnetic field lines at Alfvén radius ∼ 10 7 cm. Afte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Many models have been proposed to explain the high brightness temperate of FRBs, which usually involve magnetized compact stars as progenitors, especially neutron stars (NS) (see Platts et al 2018, for a rencent review). In particular, it is widely suggested that young flaring magnetars (Popov & Postnov (2013); Lyubarsky (2014); Waxman (2017); Beloborodov (2017); Lu & Kumar (2018); Yang & Zhang (2018); Margalit & Metzger (2018); Katz (2018); Beloborodov (2019); Metzger et al (2019); ; Margalit et al (2020); Wang & Lai (2020); Kumar & Bošnjak (2020), see also Margalit et al 2020;Lyutikov & Popov 2020;Lu et al 2020;Yu et al 2020;Katz 2020;Yang et al 2020;Yuan et al 2020, for models associated with soft gamma-ray repeaters), and old NSs under interaction with their companion (Wang et al (2016(Wang et al ( , 2018; Dai et al (2016); Zhang (2016, see also Dai 2020;Geng et al 2020, for models associated with soft gamma-ray repeaters) can be FRB progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…Many models have been proposed to explain the high brightness temperate of FRBs, which usually involve magnetized compact stars as progenitors, especially neutron stars (NS) (see Platts et al 2018, for a rencent review). In particular, it is widely suggested that young flaring magnetars (Popov & Postnov (2013); Lyubarsky (2014); Waxman (2017); Beloborodov (2017); Lu & Kumar (2018); Yang & Zhang (2018); Margalit & Metzger (2018); Katz (2018); Beloborodov (2019); Metzger et al (2019); ; Margalit et al (2020); Wang & Lai (2020); Kumar & Bošnjak (2020), see also Margalit et al 2020;Lyutikov & Popov 2020;Lu et al 2020;Yu et al 2020;Katz 2020;Yang et al 2020;Yuan et al 2020, for models associated with soft gamma-ray repeaters), and old NSs under interaction with their companion (Wang et al (2016(Wang et al ( , 2018; Dai et al (2016); Zhang (2016, see also Dai 2020;Geng et al 2020, for models associated with soft gamma-ray repeaters) can be FRB progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…• The trigger of QPOs in the neutron star crust is likely from internal, but an external trigger powered by infall of an asteroid is also possible (Dai 2020; Geng et al 2020), which might explain the rarity of the FRB-associated bursts. Such models, however, need to interpret the existence of QPOs already before the spikes associated with FRB pulses.…”
Section: Constraints On Theoretical Modelsmentioning
confidence: 99%
“…Similar behaviors between FRBs and solar type III radio bursts have been found (Zhang et al 2019). There are some theoretical works on this FRB (Margalit et al 2020a;Lu et al 2020;Lyutikov & Popov 2020;Dai 2020;Geng et al 2020;Katz 2020;Yu et al 2020;Yang et al 2020). In this paper, we focus on the synchrotron maser shock model proposed by Metzger et al (2019).…”
Section: Introductionmentioning
confidence: 99%